Estudio farmacognóstico de un extracto fluido de mático (Piper Angustifolium) para uso farmacéutico. - Vite Barrezueta, Winston J. (2008)
To elaborate a fluent extract from the leaves if piper angustifolium, that would be effective and have high quality for pharmaceutical use. The result of the fitiquímico study indicate the presence of metabolites like alkaloids, lactonas, coumarinas, resins, saponinas, phenolic, tannins and flavonoids. In addition they presented an intense olive green color and a sui generic scent (typical of the plant). A density of 0.9869-1.0227 pH de 5.60- 5.88 refractive index of 1.355 total solids 7.4-11.